Physical Conditions in the LMC’s Quiescent Molecular Ridge: Fitting Non-LTE Models to CO Emission - Finn, Molly K.; Indebetouw, Remy; Johnson, Kelsey E.; Costa, Allison H.; Chen, C.-H. Rosie; Kawamura, Akiko; Onishi, Toshikazu; Ott, Jürgen; Tokuda, Kazuki; Wong, Tony; Zahorecz, Sarolta (The Astrophysical journal, 2021)
The Molecular Ridge in the LMC extends several kiloparsecs south from 30 Doradus, and it contains ∼30% of the molecular gas in the entire galaxy. However, the southern end of the Molecular Ridge is quiescent—it contains almost no massive star formation, which is a dramatic decrease from the very active massive-star-forming regions 30 Doradus, N159, and N160. We present new Atacama Large Millimeter/submillimeter Array and Atacama Pathfinder Experiment observations of the Molecular Ridge at a resolution as high as ∼16″ (∼3.9 pc) with molecular lines 12 CO(1-0), 13 CO(1-0), 12 CO(2-1), 13 CO(2-1), and CS(2-1). We analyze these emission lines with our new multiline non-LTE fitting tool to produce maps of T kin , n H 2 , and N CO across the region based on models from RADEX . Using simulated data for a range of parameter space for each of these variables, we evaluate how well our fitting method can recover these physical parameters for the given set of molecular lines. We then compare the results of this fitting with LTE and X CO methods of obtaining mass estimates and how line ratios correspond with physical conditions. We find that this fitting tool allows us to more directly probe the physical conditions of the gas and estimate values of T kin , n H 2 , and N CO that are less subject to the effects of optical depth and line-of-sight projection than previous methods. The fitted n H 2 values show a strong correlation with the presence of young stellar objects (YSOs), and with the total and average mass of the associated YSOs. Typical star formation diagnostics, such as mean density, dense gas fraction, and virial parameter do not show a strong correlation with YSO properties.